Ecological Asessment In Semarang Coastal Area Based On Sediment Bioassay Approach Using Green Mussel Larvae - Rachma Puspitasari; Triyoni Purbonegoro (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2016)
Rapid developments of industry and population growth have lead to ecological pressures on coastal areas. Semarang as capital of Central Java and port city, has an environment sensitivity which is important to be investigated. Sediment is an important part in aquatic environment because acts as sink or source of pollutant and could be used to assess coastal environment health. Three locations had been studied, i.e. Tanjung Mas Port, estuaries of Banjirkanal Barat and Banjirkanal Timur. These locations were compared to assess their health of sediment through elutriate sediment toxicity test. Eighteen grams of sediment from each locations were weighed and placed in 1 L Beaker glass.  Eggs and sperm are taken from spawning of adult green mussel in laboratory.  Thirty mL of sperm was added to the eggs and fertilized eggs were observed microscopically. Fertilized eggs were exposure to elutriate water-sediment from each location for 48 hour. Statistical analysis showed that there are significantly different abnormalities larvae percentage of sites 5, 8 and 13. The highest percentage of abnormality larvae occurred in Port Tanjung Mas, followed by Banjirkanal Timur and Banjirkanal Barat. Lead concentrations in sediments of coastal Semarang was ranged from 10.9 to 15.62 mg.kg-1, with an average of 13.69 mg.kg-1. Lead concentration was decreased form Port, Banjirkanal Timur and Banjirkanal, respectively. The abnormalities of green mussel larva may related to lead contamination. It could be concluded that sediment quality in Port area was very poor compare than other site. Keywords: bioassay, green mussel larvae, sediment, Semarang coastal area